2015
DOI: 10.3174/ajnr.a4574
|View full text |Cite
|
Sign up to set email alerts
|

Favorable Bridging Therapy Based on DWI-FLAIR Mismatch in Patients with Unclear-Onset Stroke

Abstract: BACKGROUND AND PURPOSE:Standard selection criteria for revascularization therapy usually exclude patients with unclear-onset stroke. Our aim was to evaluate the efficacy and safety of revascularization therapy in patients with unclear-onset stroke in the anterior circulation and to identify the predictive factors for favorable clinical outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 22 publications
0
8
0
Order By: Relevance
“…However, the incidence of symptomatic intracranial bleeding was higher, and the mortality rate was not significantly increased in alteplase group when compared to a placebo. Mourand et al (2015) used the DWI/FLAIR mismatch criteria to evaluate the safety and efficacy of thrombolysis and bridging therapy (thrombolysis followed by mechanical thrombectomy) in patients with wake-up strokes. The authors revealed that 52% of patients with wake-up strokes experienced favorable outcomes (mRs score = 0-2) at three months post-thrombolysis.…”
Section: Discussionmentioning
confidence: 99%
“…However, the incidence of symptomatic intracranial bleeding was higher, and the mortality rate was not significantly increased in alteplase group when compared to a placebo. Mourand et al (2015) used the DWI/FLAIR mismatch criteria to evaluate the safety and efficacy of thrombolysis and bridging therapy (thrombolysis followed by mechanical thrombectomy) in patients with wake-up strokes. The authors revealed that 52% of patients with wake-up strokes experienced favorable outcomes (mRs score = 0-2) at three months post-thrombolysis.…”
Section: Discussionmentioning
confidence: 99%
“…Only some patients (11% and 5%, respectively) received bridging therapy in the endovascular treatment arm of the DEFUSE-3 (11%) and DAWN (5%) trials [4,5]. In a different study, bridging therapy (n = 19) versus direct IVT (n = 21) was associated with 3-month favorable outcome in patients with large vessel occlusion in the anterior circulation and DWI/FLAIR-MRI mismatch [10].…”
Section: Discussionmentioning
confidence: 99%
“…Several investigators have used this concept of DWI-FLAIR mismatch to guide thrombolytic therapy in WUS. [78][79][80] Outcomes in these patients in general were favorable and indicated that persons with WUS and DWI-FLAIR mismatch without contraindication to thrombolytic therapy may indeed benefit from this therapy without having excess risk of symptomatic hemorrhage.…”
Section: Magnetic Resonance Imaging (Mri) In Wusmentioning
confidence: 91%